2016
DOI: 10.1161/jaha.116.003768
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation and the Risk of Cardiovascular Diseases: A Meta‐Analysis of Randomized Controlled Trials

Abstract: BackgroundResults from observational and genetic epidemiological studies suggest that lower serum homocysteine levels are associated with lower incidence of cardiovascular disease (CVD). Numerous randomized controlled trials have investigated the efficacy of lowering homocysteine with folic acid supplementation for CVD risk, but conflicting results have been reported.Methods and ResultsThree bibliographic databases (Medline, Embase, and the Cochrane Database of Systematic Reviews) were searched from database i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(134 citation statements)
references
References 72 publications
6
124
1
3
Order By: Relevance
“…Our findings were consistent with the prior studies mentioned above. Furthermore, our findings were also supported by several previous clinical trials, which indicated that antihomocysteine therapy (eg, folic acid supplementation) was effective in reducing BPs and the risk of cardiovascular diseases . For example, a meta‐analysis of 12 randomized controlled clinical trials found that supplementation with 5000 to 10 000 μg/d of folate for at least 6 weeks could lower SBP by 2.03 mm Hg .…”
Section: Discussionsupporting
confidence: 85%
“…Our findings were consistent with the prior studies mentioned above. Furthermore, our findings were also supported by several previous clinical trials, which indicated that antihomocysteine therapy (eg, folic acid supplementation) was effective in reducing BPs and the risk of cardiovascular diseases . For example, a meta‐analysis of 12 randomized controlled clinical trials found that supplementation with 5000 to 10 000 μg/d of folate for at least 6 weeks could lower SBP by 2.03 mm Hg .…”
Section: Discussionsupporting
confidence: 85%
“…In more recent years, however, evidence is emerging to suggest that the achievement of optimal folate status may be important not only for women of child-bearing age, but for the general population. This is due to the increased recognition of the potential protective role of folate in the primary prevention of cardiovascular disease, particularly stroke [3,4], age-related cognitive impairment [5,6] and osteoporosis [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a positive association was found between reduction in Hcy levels and the beneficial effect associated with folic acid therapy. [34,37] There is substantial variability in Hcy levels even within the population without folic acid fortification. [13] Therefore, from a research and population-health perspective, it is important to clarify whether there are certain subgroups of individuals who had higher Hcy levels and might benefit from Hcy-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%